The Effect of Using Ankidroid on Cognitive Learning Outcomes of Islamic Religious Education - Rifai, Ikhsan; Nurhaliza (Eduscape : Journal of Education Insight, 2024)
Islamic religious education learning which emphasizes rote learning often causes students to feel bored and lack interest in learning. Students' efforts to memorize material tend to be unstructured and less systematic. The aim of this research is to determine the influence of flashcard media and AnkiDroid on the cognitive outcomes of Islamic Religious Education on the material Rahmat Islam for the Archipelago in Class XII SMA Negeri 1 Kasihan and to make a comparison between the two. This research makes a contribution by exploring the effectiveness of two learning media in improving PAI learning outcomes. To the best of the author's knowledge, there has been no research that specifically compares conventional flashcards with AnkiDroid in the context of PAI subjects. This research uses a quantitative approach with an experimental method with a quasi-experimental research design, namely a nonequivalent control group design. The research results show that both media, both flashcards and AnkiDroid, have a significant influence on PAI's cognitive learning outcomes in the Rahmat Islam Untuk Nusantara material. Nonetheless, there is no significant difference between the two.